Co-occurrence of dual lineages within Simulium (Gomphostilbia) atratum De Meijere in the Indonesian Archipelago along Wallace's Line - Hew, Yan Xin (Elsevier, 2024)
Mitochondrial cytochrome c oxidase subunit I (COI) sequences were utilized to infer the population genetic structure of Simulium (Gomphostilbia) atratum De Meijere, an endemic simulid species to Indonesia. Both median joining haplotype network and maximum-likelihood tree revealed two genetic lineages (A and B) within the species, with an overlap distribution in Lombok, which is situated along Wallace's line. Genetic differentiation and gene flow with varying frequencies (FST = 0.02-0.967; Nm = 0.01-10.58) were observed between populations of S. (G.) atratum, of which population pairs of different lineages showed high genetic differentiation. Notably, the high genetic distance of up to 5.92 % observed within S. (G.) atratum in Lombok was attributed to the existence of two genetically distinct lineages. The co-occurrence of distinct lineages in Lombok indicated that Wallace's line did not act as faunistic border for S. (G.) atratum in the present study. Moreover, both lineages also exhibited unimodal distributions and negative values of neutrality tests, suggesting a pattern of population expansion. The expansion and divergence time estimation suggested that the two lineages of S. (G.) atratum diverged and expanded during the Pleistocene era in Indonesia.